THE EXTENT OF EXPOSURE OF BAGHDAD UNIVERSITY : (Students To Cultural And Television Programs) - Mtashar Abdul-Saheb, Saad (ALBAHITH ALALAMI, 2022)
Communication is one of the main elements of culture, it is the source of its formation and a factor of its development and spread. Communication is a ’dynamic’ cultural process and is an integral part of the political, social, economic and cultural aspects of people. Therefore, mass communication means help in the course and movement of individuals and cultural communities. The relationship between media and culture according to this perspective is one of many key factors and influential forces that make it coherent and sometimes intertwined. It is a problematic relationship that leads to research and study in order to lay the right foundations in the orientation towards the audience. Mass communication has many basic functions. UNESCO has approved the following functions: • Information • Socialization • Creating motives • Dialogue and debate • Integration • Education • Entertainment • Satisfy the needs of the individual and the community • Cultural advancement Accordingly, it is not possible to say that mass communication is an embodiment of the culture of society and an expression of the values ​​and standards derived from this culture, which confirms the importance of those in contact with the reference cultures of society and its various segments, as well as their knowledge of the psychological composition of those segments and their knowledge of their needs of TV programs, their wishes and desires. In addition, the performance and cultural function of communication means requires those involved in this activity to master a variety of events and cultural contents at the same time, in order to be able to understand the sophisticated art and absorb the ideas and cultural aspects then submit it.